The aesthetics of imagination in design - Folkmann, Mads Nygaard 1972-
In The Aesthetics of Imagination in Design, Mads Folkmann investigates design in both material and immaterial terms. Design objects, Folkmann argues, will always be dual phenomena?material and immaterial, sensual and conceptual, actual and possible. Drawing on formal theories of aesthetics and the phenomenology of imagination, he seeks to answer fundamental questions about what design is and how it works that are often ignored in academic research